2001
DOI: 10.1124/mol.59.6.1426
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Treatment of C6 Glioma Cells with Antidepressant Drugs Results in a Redistribution of Gsα

Abstract: Previous studies have demonstrated that chronic treatment of C6 glioma cells with the antidepressants desipramine and fluoxetine increases the Triton X-100 solubility of the G protein Gs␣ . The antidepressants also caused a 50% decrease in the amount of Gs␣ localized to caveolae-enriched membrane domains. In this study, laser scanning confocal microscopy reveals that Gs␣ is localized to the plasma membrane as well as the cytosol in both treated and control cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
29
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 32 publications
6
29
0
Order By: Relevance
“…These studies have demonstrated that G sα is localized to TX-100-resistant membrane domains and the tips of elongated processes of C6 glioma cells, and this localization is altered after chronic antidepressant treatment [14][15][16]. Similarly, we have observed an altered distribution of G sα in the TX-100-resistant and the TX-100-soluble membrane domains in the prefrontal cortex and cerebellum of depressed suicide subjects compared with control subjects [17].…”
supporting
confidence: 52%
See 1 more Smart Citation
“…These studies have demonstrated that G sα is localized to TX-100-resistant membrane domains and the tips of elongated processes of C6 glioma cells, and this localization is altered after chronic antidepressant treatment [14][15][16]. Similarly, we have observed an altered distribution of G sα in the TX-100-resistant and the TX-100-soluble membrane domains in the prefrontal cortex and cerebellum of depressed suicide subjects compared with control subjects [17].…”
supporting
confidence: 52%
“…In summary, previous studies in both rats and C6 glioma cells demonstrated that chronic antidepressant treatment liberates G sα , but not G iα or G oα , from the inhibitory TX-100-resistant membrane raft domains [14][15][16], increasing its Progress toward a depression biomarker -EDITORIAL future science group future science group www.futuremedicine.com association with adenylyl cyclase [16]. Coupled with postmortem human brain data, these observations demonstrate that the increased localization of G sα in the TX-100-resistant membrane domains of depressed individuals may prevent G sα from associating with and activating adenylyl cyclase, thus preventing the propagation of the cAMP signal.…”
mentioning
confidence: 99%
“…This has been observed in both rats (7) and cell culture (8,16,30). Moreover, lipid raft disruption through cholesterol depletion or cytoskeletal disruption displaces many raft proteins, but GPCR activation or antidepressant treatment displaces only G␣ s (7).…”
Section: Discussionmentioning
confidence: 93%
“…Although it is not possible to directly compare the timedependent effect seen in in vivo experiments with that obtained in vitro, it should be stressed that similar changes as those observed after long-term administration of psychotropic drugs in experimental animals are also present in vitro after their 3-5-days presence (depending on concentration) in culture medium (Donati et al, 2001;Lai et al, 2003). Since no data are available on the effect of chronic treatment with particular antipsychotic drugs on CRH concentration in vivo, the present results can be related only to antipsychotic-induced changes in corticosterone blood level.…”
Section: Discussionmentioning
confidence: 99%